2019
DOI: 10.1016/j.tics.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Readers Are Parallel Processors

Abstract: Reading research has long endorsed the view that words are processed strictly one by one. The primary empirical test of this notion is the search for effects from upcoming words on readers' eye movements during sentence reading.Here we argue that no conclusions can be drawn from the absence of such effects, and that the serial versus parallel processing debate cannot be resolved without treading beyond the methodological scope of tracking eye movements. Recent considerations of how the brain organizes linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 79 publications
4
88
2
Order By: Relevance
“…Interestingly, they sometimes report letters that were present in the other word. This type of "migration" error is sensitive to high-level lexical properties, and has been taken as evidence of parallel word recognition (McClelland & Mozer, 1986;Mozer, 1983;Snell & Grainger, 2019b). Again, however, the time between the onset of the words and the post-masks in those experiments was quite long, on the order of 200-500 ms.…”
Section: Distinguishing Parallel and Serial Modelsmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, they sometimes report letters that were present in the other word. This type of "migration" error is sensitive to high-level lexical properties, and has been taken as evidence of parallel word recognition (McClelland & Mozer, 1986;Mozer, 1983;Snell & Grainger, 2019b). Again, however, the time between the onset of the words and the post-masks in those experiments was quite long, on the order of 200-500 ms.…”
Section: Distinguishing Parallel and Serial Modelsmentioning
confidence: 94%
“…The debate has recently extended beyond oculomotor measures during reading (Snell & Grainger, 2019b). For instance, several studies have shown that with relatively short displays (≤ 200 ms) word recognition performance is influenced by surrounding words and sentence context (Snell, Declerck, & Grainger, 2018a;Snell, Meeter, & Grainger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they sometimes report letters that were present in the other word. This type of "migration" error is sensitive to high-level lexical properties, and has been taken as evidence of parallel word recognition (McClelland & Mozer, 1986;Mozer, 1983;Snell & Grainger, 2019). Again, however, the time between the onset of the words and the post-masks in those experiments was quite long, on the order of 200-500 ms.…”
Section: Distinguishing Parallel and Serial Modelsmentioning
confidence: 94%
“…The debate has recently extended beyond oculomotor measures during reading (Snell & Grainger, 2019). For instance, several studies have shown that with relatively short displays (<=200 ms) word recognition performance is influenced by surrounding words and sentence context (Snell, Declerck, & Grainger, 2018;Snell, Meeter, & Grainger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the letters of visual words up to a certain length can be processed in parallel, unlike the sequential unfolding of sounds in spoken language (Adelman, Marquis, & Sabatos-DeVito, 2010;Radeau, Morais, Mousty, Saerens, & Bertelson, 1992). There are also indications that more than one word can be processed simultaneously in reading (Snell & Grainger, 2019), and it has been argued that reading enables better prediction of upcoming words (Huettig & Pickering, 2019). All these factors help to understand why reading can be faster than listening.…”
Section: Hypotheses Of Why Reading Is Faster Than Listeningmentioning
confidence: 99%